The Factors of Decision in Taking Tertiary Education - Lailiyah, Alfi Nur; Priyarsono, Dominicus Savio; Probokawuryan, Mutiara (AFEBI Economic and Finance Review, 2017)
The decision to access tertiary education is influenced by individual characteristics, household characteristics, and regional factors. This study aimed to examine the determinant of  individual decision to access tertiary education based on individual characteristics, household characteristics, and regional factors. The respondents of the study were 19 years old or above and already finished secondary education. This study used secondary data from data Indonesian Family Life Survey (IFLS) 5. Technique analysis used multinominal logit by samples that consist of 1.936 respondent. The result of this analysis showed that the individual characteristic that consist of UN score, Sex, and Occupational status while study has significant impact on the choice to access undergraduate study. Likewise, on the household characteristics that consist of educational assistance from non government, level of education of  head of household, and the consumption per member of the family has significant impact to the choice to access diploma. In undergraduate education, only the UN score in individual characteristic that has significant impact. The household characteristics were consist of educational assistance from government and non-government, the level of education of head of household, the consumption per member of the family, and dependency ratio impact significantly on the choice to access undergraduate study.JEL Classification: I20, I21, I25Keywords: Household Characteristics, Individual Characteristics, Indonesia Family Life Survey, Multinomial Logit, Regional Factors, Tertiary Education